Rules for the revision of the constitution in the European states - Maslovskaya, Tatiana S. (Journal of the Belarusian State University. Law, 2022)
The article discusses the rules for constitutional revision, including requirements related to the procedure for constitutional revision, as well as requirements related to the subject of constitutional revision. The factors influencing the «set» of revision rules included in the constitutional text are analysed. Attention is paid to the elements of a hard procedure for reviewing the constitution. The requirements related to the time of revision, certain circumstances and the content of the revised norms are examined. The analysis is based on the experience of European states.
Keywords: constitution; revision of the constitution; constitutional revision rules; limits to constitutional revision; European countries